2018
DOI: 10.3390/ijerph15030548
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Crab Ponds of Lake Guchenghu Basin, China: Occurrence, Temporal Variations, and Ecological Risks

Abstract: Antibiotics are widely used in aquaculture, however, this often results in undesirable ecological effects. To evaluate the occurrence, temporal variations, and ecological risk of antibiotics in five crab ponds of Lake Guchenghu Basin, China, 44 antibiotics from nine classes were analyzed by rapid resolution liquid chromatography-tandem mass spectrometry (RRLC-MS/MS). Twelve antibiotics belonging to six classes were detected in the aqueous phase of five crab ponds, among which sulfonamides and macrolides were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
3
3
Order By: Relevance
“…Reference [24], also reported a temperature range of 26-29 0 C and opined that such temperature range supports fish productivity. Contrary to our findings [25], reported much lower temperature, below 25°C, in their study on occurrence, temporal variations, and ecological risks of use of antibiotics in crab ponds of Lake Guchenghu Basin, China.…”
Section: Discussioncontrasting
confidence: 99%
“…Reference [24], also reported a temperature range of 26-29 0 C and opined that such temperature range supports fish productivity. Contrary to our findings [25], reported much lower temperature, below 25°C, in their study on occurrence, temporal variations, and ecological risks of use of antibiotics in crab ponds of Lake Guchenghu Basin, China.…”
Section: Discussioncontrasting
confidence: 99%
“…Makori et al [21] reported temperature and pH range of 24-26 °C, and pH 6.1-8.3, respectively. A study conducted in Kenya, reported a temperature range from 20.04˚C to 32.63˚C [24], elsewhere, the temperature was lower than in the present study [7]. Rapid and fluctuating changes in pH and temperature have been reported to cause extreme stress in the fish.…”
Section: Discussioncontrasting
confidence: 47%
“…The contamination of these culture systems has been attributed to poor water quality, high stocking densities and the use of animal manure and contaminated feed [6,5] Due to the high cost of feeding, farmers use animal manure to supplement feeding. The use of organic manure also leads to the release of high concentration of opportunistic and pathogenic microorganisms into the ponds, which pose a threat not only to fish health but also to the environment [7]. Also, these microorganisms in fish and fish ponds portend grave consequences for public health [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Optimum pH and temperature directly stabilise the physicochemical parameters of pond water enhancing fish health, and productivity and the maintenance of a proper balance of the microbial ecology in pond water. A study conducted in Kenya, reported a temperature range from 20.04˚C to 32.63˚C [6], elsewhere, the temperature was lower than in the present study [9]. Rapid and fluctuating changes in pH and temperature have been reported to cause extreme stress in the fish.…”
Section: Discussioncontrasting
confidence: 47%
“…Due to the high cost of feeding, farmers use animal manure to supplement feeding. The use of organic manure also leads to the release of high concentration of opportunistic and pathogenic microorganisms into the ponds which pose a threat not only to fish health but the environment [9]. Also, these microorganisms in fish and fish ponds portend grave consequences for public health [4,5].…”
Section: Introductionmentioning
confidence: 99%